The depository stocks of the United Nations and its specialized organizations in the USSR - Balsytė, Raimunda (Knygotyra, 1987)
In the beginning of the article the author analyses the depository stocks of the United Nations in the libraries which for some years were the depositories of this organization. A more detailed characteristics is given to the depository stocks of the United Nations and its specialized organizations, which are functioning in our country nowdays. The recommendations about a better development of these stocks are given in the article, too.